Pengaruh Praktik Kewirausahaan Dan Lingkungan Sekolah Terhadap Minat Menjadi Wirausaha Siswa Fase F Di SMK Negeri 5 Padang - Martarisa Delarani; Dessyta Gumanti; Serli Diovani Teza (JURNAL ARMADA PENDIDIKAN, 2025)
This study investigates the influence of entrepreneurial practice and the school environment on students’ interest in becoming entrepreneurs at SMK Negeri 5 Padang. The problem addressed in this research is the low interest of students in entrepreneurship despite the implementation of entrepreneurial practice and the availability of a supportive school environment. The study aims to analyze the effect of entrepreneurial practice, the effect of the school environment, and the combined effect of both factors on entrepreneurial interest. The research applies a quantitative method with a descriptive-associative approach, involving a population of 265 students and a sample of 159 students selected through stratified proportionate random sampling. Data were collected using a questionnaire tested for validity and reliability, and analyzed through multiple linear regression with the assistance of SPSS. The findings reveal that entrepreneurial practice has a positive and significant effect on students’ entrepreneurial interest, the school environment also has a positive and significant effect, and both factors together significantly enhance students’ interest in entrepreneurship. These results indicate that effective entrepreneurial practice supported by a conducive school environment can substantially increase students’ motivation to pursue entrepreneurship.